Moringa Leaf (Moringa oleifera Lam) Nanoparticle Supplementation on Zygote Cleavage in Goat Embryo Culture In Vitro - Alfina Aisatus Saadah1 , Widjiati2 , Hendy Hendarto3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
One of the causes of failure of zygote development is oxidative stress in the culture medium. Where oxidative stress can damage the structure and function of zygotes due to free radicals Reactive Oxygen Species (ROS). Moringa oleifera Lam contains antioxidant polyphenol compounds, flavonoid flavanols namely quercetin which is the most antioxidant content in Moringa leaves which is expected to fight excess ROS. The purpose of this study was to prove that the supplementation of Moringa oleifera Lam leaf nanoparticles to increase zygote cleavage in goat embryo culture in vitro. The research subjects used goat oocytes which were divided into 4 groups consisting of 1 control group and 3 treatment groups. Each group consisted of 31 samples. Control group K1 without Moringa leaf nanoparticle supplementation, treatment group I P1 Moringa leaf nanoparticle supplementation with a dose of 0.5 µM, treatment group II P2 supplementation of Moringa leaf nanoparticles with a dose of 1.0 µM, Treatment group III P3 supplementation with Moringa leaf 2.0 µM. Embryo culture was carried out in a 5% CO2 incubator, temperature 38.5ºC for 48 hours, then observed under an inverted microscope. The results show that there are significant differences with the value of p = 0.041 which means p <0.05. Supplementation of moringa leaf nanoparticles (Moringa oleifera Lam) can significantly increase zygote cleavage at embryo culture stage in vitro.